2007
DOI: 10.1103/physrevlett.98.049902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: ac Stark Shift and Dephasing of a Superconducting Qubit Strongly Coupled to a Cavity Field [Phys. Rev. Lett.94, 123602 (2005)]

Abstract: Figure 5a in the Letter presents the ac Stark shift of a Cooper pair box inside a coplanar waveguide resonator as a function of microwave probe power driving the resonator. Within lowest order perturbation theory, the corresponding cavity photon number is linear in the drive power. The photon number fit to the data using Eq. (1) in the Letter is shown in Fig. 5a. Lowest order perturbation theory is expected to break down [1] on the scale of the critical photon number n c 2 =4g 2 82. This breakdown is not visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
163
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(175 citation statements)
references
References 2 publications
11
163
1
Order By: Relevance
“…[16][17][18][19][20] These authors demonstrated that previously quantum mechanically explained single-or multiphoton resonance, the effective barrier suppression, and the Rabi oscillation can also be understood from the classical point of view. Interpretations on both the classical and quantum bases are also reported [19][20][21][22] for the results involving multiphoton, multilevel Rabi oscillation, and ac Stark shift at high W. [21][22][23][24] It is found that at high W, the predictions of the classical and quantum pictures may converge. 22 These results indicate that the Josephson junction system can have a dual character, classical and quantum mechanical, when a microwave field is applied.…”
Section: Introductionmentioning
confidence: 92%
“…[16][17][18][19][20] These authors demonstrated that previously quantum mechanically explained single-or multiphoton resonance, the effective barrier suppression, and the Rabi oscillation can also be understood from the classical point of view. Interpretations on both the classical and quantum bases are also reported [19][20][21][22] for the results involving multiphoton, multilevel Rabi oscillation, and ac Stark shift at high W. [21][22][23][24] It is found that at high W, the predictions of the classical and quantum pictures may converge. 22 These results indicate that the Josephson junction system can have a dual character, classical and quantum mechanical, when a microwave field is applied.…”
Section: Introductionmentioning
confidence: 92%
“…To understand how the qubit-collective modes interactions can affect coherence, let us briefly review the so-called photon shot noise (or measurement-induced) dephasing, originating from the interaction between a qubit and the electromagnetic modes of the cavity in which it is placed [28,29]. As a consequence of this coupling, the qubit frequency ω 10 depends on the occupation of the cavity modes ω 10 ({n μ }) = ω 10 + 2 μχ μ n μ , (1) where n μ is the occupation number of mode μ andχ μ denotes the dispersive shift of that mode.…”
Section: Collective Modes and Qubit Dephasingmentioning
confidence: 99%
“…The magnitude of the rate agrees well with the theory, extracting a coupling constant C µ /C Σ ≈ 0.02 which agrees with measured circuit parameters. We include in the fit the effects of inhomogenous broadening of the dressed state resonance, which can be caused by photon number fluctuations in the oscillator [25]. To estimate this effect, we start with the frequency shift per photon g 2 osc /πδω ≈ 26 MHz, where g osc /2π ≈ 15 MHz is the qubit-oscillator coupling and we have used δω = 2πf c /Q.…”
mentioning
confidence: 99%